EFEKTIVITAS LATIHAN AEROBIK DALAM MENINGKATKAN DAYA TAHAN KORDIORESPIRASI (VO2MAX) PADA PESERTA DIDIK DIKELAS X MAN 1 - Manalu, Nimrot; Manami Aprianto Samosir; Muhammad Yudha Pratama; Rido Pandu Hutasoit; Sarto Greos Damanik (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Physical fitness, particularly cardiorespiratory endurance, is an important aspect in supporting students’ learning activities and health. However, many students still have low levels of physical activity, resulting in inadequate VO₂ Max capacity. This study aimed to determine the effectiveness of aerobic exercise in improving cardiorespiratory endurance (VO₂ Max) among tenth-grade students at MAN 1 Medan. The study used a quantitative approach with a one-group pre-test and post-test experimental design. The sample consisted of 20 students selected from class X MAN 1 Medan. Data were collected through VO₂ Max tests conducted before and after aerobic exercise training. The results showed that all participants experienced an increase in VO₂ Max after the training program. The average pre-test score was 31.58 and increased to 35.90 in the post-test, with an average improvement of 4.32. These findings indicate that aerobic exercise is effective in enhancing students’ cardiorespiratory endurance. The results of this study are consistent with previous studies stating that aerobic exercise and interval training contribute positively to improving VO₂ Max and physical fitness.